Empowering the employability of people with disability (PWD) through a skills intervention program - Omar, Muhd Khaizer; Mohd Puad, Mohd Hazwan; Yaakub, Mohamad; Muslim, Marlinah; Gui, Qing (South East Asian Association for Institutional Research, 2024)
People with disability (PWD) are a unique group who possess special virtuosity. Through employers' feedback from a survey that was conducted, a skill intervention program was designed and conducted by employing a reskilling and upskilling module that was aligned to employers’ job requirements among selected PWDs at the Putra Future Classroom (PFC), Universiti Putra Malaysia. Prior to the program, an ethical approval form was sent and approved by the ethics board of the university, and selected employers were asked to respond to a quantitative survey to obtain their insights on employability skills traits necessary for today’s job market. In the program, the group of PWDs spent three days with employability skill trainers and certified image consultants. A single case study semi-structured interview session was then conducted with the PWDs after the program to gather their personal experiences. In addition, a focus group discussion (FGD) was conducted with 30 students who were selected through purposive sampling. This was done through validated and established openended questions that were asked asynchronously via the WhatsApp instant messaging application as physical interview sessions were not feasible due to the COVID-19 pandemic. The text and audio responses were recorded and transcribed using the Atlas.ti software. Constant comparative analysis was employed through the use of the color-coded technique to develop the themes. The process of triangulation involved module, fieldnotes, and observation prior, during, and after the project completion. Based on the findings, it was found that PWDs do well in employment, highlighting the importance of reviewing the plethora of skeptical beliefs given the fact that employability skills are intrinsic values that involve non-technical and less physical functions. The process of integrating PWDs in the workforce is thus crucial to ensure that no one is left behind and that the country's wealth and prosperity are not compromised.